The Role of Digital Literacy in Countering Hoax News Among Generation Z: A Systematic Literature Review - Dayang Ratna Filynesia; Cahyo Hasanudin; Ernia Duwi Saputri; Puput Suriyah (Jurnal Pendidikan Edutama, 2026)
Digital literacy is an essential skill in the modern era for understanding information and using digital media effectively. The purpose of this study is to determine the role of digital literacy in combating hoaxes among Generation Z. This study uses secondary data from national journals. Data collection techniques use the read-and-record method. Data validation techniques use triangulation. The results of the survey indicate that digital literacy in combating hoax news among Generation Z has three roles: 1) helping to improve digital literacy among Generation Z, 2) developing verification and information literacy skills, and 3) strengthening understanding of digital ethics and responsibility. This study concludes that there are three roles of digital literacy in combating hoax news among Generation Z.